Teak (Tectona grandis) decay associated with Verticillium sp. and Fomes sp. within reforestation areas in Côte d'Ivoire - Wahounou, P. J. (2019)
Teak (Tectona grandis) occupies a significant place for reforestation in Cote d’Ivoire. Recently, there has been a resurgence of withering in different forestry areas, which represents a serious threat to the profitability and survival of forest plantations. A study has been undertaken to resolve this problem. Plant samples were collected from the trunk (bark, sapwood and central cylinder) and the roots for fungal microflora analysis through in vitro cultures to identify the causative agent of the decay of healthy trees. Sixteen different fungal genera were selected, including two species responsible for teak disease: Verticillium sp. with 82% and 98% frequencies and Fomes sp. with 79% and 60% frequencies, respectively in the roots and trunks of the diseased teaks. The presence of fungi was recorded as Verticillium sp. in 30% of diseased trees, Fomes sp. in 7.5% and all species combined in 70.5% of the cases. The inoculation of young seedling teaks in semi-controlled environment with isolates of different species of fungi allowed the restoration of the infection over 73.3% of the plants with Verticillium sp. and 16.4% with Fomes sp. The study recorded, for the first time, Verticillium sp. responsible for teak decay in plantation and reforestation (semi deciduous dense forest environment) in Cote d’Ivoire. Very often the causes of teak and forest species decay associated with fungi are attributed by error to Fomes sp., ignoring a formidable decay agent in forestry, the Verticillium sp. The lack of knowledge and information on the real causality of teak decay, associated with fungi, could make fungicidal treatments, for control of wood tree diseases, difficult and unsuccessful.